JAPANESE GOVERNMENT REASONS BEHIND THE REMOVAL OF SOUTH KOREA FROM PREFERENTIAL WHITELIST: A MERCANTILISM PERSPECTIVE - Rafidhia Putri Hendarjat; Arie Kusuma Paksi (Jurnal Studi Diplomasi dan Keamanan, 2022)
After a series of mutual whitelist exemption between the East Asian countries, Japan and South Korea since the second half of 2019, the happening of trade dispute cannot be avoided. This study aims to find the reasons behind the Japanese government decision to remove South Korea from Japan’s preferential whitelist. Through qualitative method, this study uses the mercantilism perspective of International Political Economy (IPE) combined with historical perspective of Japan and South Korea since their first encounter during the timeline of World War until the present day, especially through economic context as the theoretical framework. Therefore, this study asserts that Japan, as a country which claimed that it applied trade liberalization, also have the mercantilism ideas projection on their foreign policy by intervening the economic activities of the state, in which economy – as a form of soft power – is a crucial factor to make Japan as a strong state and crucial actor in international political stage, as the rivalry in global technology market with South Korea and strategic alliance with the United States needs to be prioritized by the Japanese government in order to protect its national interest as a state with a strong economy power after the massive economic growth of its fellow East Asian country, South Korea, and the high interdependency with South Korea especially in the 2000s era. The hypothesis can be proven through the weakening of South Korea technology and electronic integrated circuit export after their removal from Japan’s preferential whitelist and the growing favoritism by the United States, which made the Japanese government successfully achieve their national interest.